2015
DOI: 10.4103/2141-9248.165246
|View full text |Cite
|
Sign up to set email alerts
|

To assess sleep quality among pakistani junior physicians (house officers): A cross-sectional study

Abstract: Background:Sleep deprivation among junior physicians (house officers) is of growing concern. In developed countries, duty hours are now mandated, but in developing countries, junior physicians are highly susceptible to develop sleep impairment due to long working hours, on-call duties and shift work schedule.Aim:We undertook the study to assess sleep quality among Pakistani junior physicians.Subjects and Methods:A cross-sectional study was conducted at private and public hospitals in Karachi, Pakistan, from Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…. This is consistent with previous studies, 15 and might be related to the different physiological periods that females are exposed to, such as menstruation and pregnancy. 8 Additionally, previous studies noted that females tend to have more sleep related complaints in general.…”
Section: Discussionsupporting
confidence: 93%
“…. This is consistent with previous studies, 15 and might be related to the different physiological periods that females are exposed to, such as menstruation and pregnancy. 8 Additionally, previous studies noted that females tend to have more sleep related complaints in general.…”
Section: Discussionsupporting
confidence: 93%
“…For example, in a sample of US doctors working in the emergency room, Machi et al reported that the prevalence of poor sleep quality was 31% [36]. Another study in Pakistan reported that poor sleep quality was 37% among physicians [37]. A recent study in the region, in Saudi Arabia, reported that 51% of primary care physicians had poor sleep quality [38].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses, in general, as an occupational group, are subjected to multiple stressors [43]. Additionally, women are more likely to complain of sleep problems [36,37], stress, and neuropsychiatric complaints and somatoform disorders, such as headache, depression, and anxiety [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…To improve work environment, proper work schedules should be considered allowing for the mandated time off. 83 Insomnia can be treated pharmacologically; melatonin can help in the facilitation of normalizing the aberrant circadian rhythm. 84 Benzodiazepine receptor agonist response is good among several insomniac patients and remission rates are very low.…”
Section: Management Of Insomnia Better Sleep Better Functioning Rementioning
confidence: 99%